The last flight of F/O Tadeusz Stabrowski. Identification of the polish pilot - Lisman, Dagmara; Drath, Joanna; Teul, Iwona; Zielińska, Grażyna; Szargut, Maria; Dowejko, Joanna; Cytacka, Sandra; Piątek, Jarosław; Ambroziak, Jan; Śliżewski, Grzegorz; Ossowski, Andrzej (Frontiers in Genetics, 2023)
The paper presents the process of identifying an unnamed soldier of the Polish armed forces in the west, whose remains were found in a nameless grave at the municipal cemetery in Le Crotoy in France. The Polish Genetic Database of Victims of Totalitarianism team carried out the research in cooperation with the Ministry of Culture and National Heritage. A comprehensive analysis of autosomal and Y-STR markers was performed. Historical, anthropological, and forensic examinations of the remains were also carried out. The items found with the remains were also examined. Identification based on DNA analysis made it possible to restore the identity of the Polish pilot who died on 11, March 1943 near the French coast, F/O Tadeusz Stabrowski. The airman regained his name in 2018, he was about 26 years old at the time of his death and left behind a grieving wife and son in the UK. The success of identifying the NN remains was guaranteed by the appointment of an interdisciplinary team consisting of specialists in archaeology, anthropology, history, forensic medicine and forensic genetics. The analysis of historical sources allowed to determine 4 missing airmen whose remains could have been buried in the cemetery in Le Crotoy. An interesting aspect of the research was the cooperation with history enthusiasts and fans of Polish aviation, thanks to which it was finally possible to narrow down the group of pilots sought and reach the family of Tadeusz Stabrowski, who submitted comparative material for research. This is the first case of establishing the identity of a Polish pilot killed in France. Many institutions have been involved in the project, including Polish Ministry of Culture and National Heritage (MDiKN), which partially funded the research